Clinical management of cementifying fibroma: A case report and pertinent review of the current literature - Aysegul Erten Tayşi; Mert Taysi; Zuhal Yurdabakan; Fatma Nihan Aksakallı; Vakur Olgac (Ķazaķstannyṇ Klinikalyķ Medicinasy, 2022)
Cementifying fibroma is an uncommon neoplasm composed by varying amounts of cementum, bone and fibrous tissue. As a results of having similar histolological features based on inactive-looking odontogenic epithelium embedded in a fibrous stroma, it is often hard to differentiate from other fibro-osseous lesions such as fibrous dyplasia and calcifying odontogenic tumor. At this point, it is undoubtedly clear that proper radiological and clinical diagnosis play a great role together in identification. We present a rare case of this entity along with a number of clinical and radiographic features that set it apart from other pathologies mimicking fibro-osseous lesions.